The Library of Aḥmad Pasha al-Jazzār : Book Culture in Late Ottoman Palestine - Aljoumani, Said,; Burak, Guy,; Hirschler, Konrad, (Islamic History and Civilization ;, 2025)
This study is the first to examine the history and composition of the library of Aḥmad Pasha al-Jazzār (d. 1804), the famous governor of northern Palestine in the late eighteenth century, on the basis of the inventory of the library's holdings. The chapters in the first volume situate the library, one of the largest in Palestinian history prior to the end of the nineteenth century, in its historical context, examine the materiality of the collection based on a study of the extant manuscripts and other historical sources, and analyse the contents of the library. The second volume consists of a facsimile of the inventory, a critical edition and index.